Collaboration enhances later individual memory for emotional material. Issue 5 (28th May 2017) - Bärthel, Gwennis A.; Wessel, Ineke; Huntjens, Rafaële J. C.; Verwoerd, Johan
ABSTRACT: Research on collaborative remembering suggests that collaboration hampers group memory (i.e., collaborative inhibition), yet enhances later individual memory. Studies examining collaborative effects on memory for emotional stimuli are scarce, especially concerning later individual memory. In the present study, female undergraduates watched an emotional movie and recalled it either collaboratively ( n = 60) or individually ( n = 60), followed by an individual free recall test and a recognition test. We replicated the standard collaborative inhibition effect. Further, in line with the literature, the collaborative condition displayed better post-collaborative individual memory. More importantly, in post-collaborative free recall, the centrality of the information to the movie plot did not play an important role. Recognition rendered slightly different results. Although collaboration rendered more correct recognition for more central details, it did not enhance recognition of background details. Secondly, the collaborative and individual conditions did not differ with respect to overlap of unique correct items in free recall. Yet, during recognition former collaborators more unanimously endorsed correct answers, as well as errors. Finally, extraversion, neuroticism, social anxiety, and depressive symptoms did not moderate the influence of collaboration on memory. Implications for the fields of forensic and clinical psychology are discussed.